Management of intracranial tuberculous mass lesions: How long should we treat for? - Marais, S; Van Toorn, R; Chow, FC; Manesh, A; Siddiqi, OK; Figaji, A; Schoeman, JF; Meintjes, G; Donovan, J; Hamers, RL; Thuong, NTT (F1000Research, 2019)
Tuberculous intracranial mass lesions are common in settings with high tuberculosis (TB) incidence and HIV prevalence. The diagnosis of such lesions, which include tuberculoma and tuberculous abscesses, is often presumptive and based on radiological features, supportive evidence of TB elsewhere and response to TB treatment. However, the treatment response is unpredictable, with lesions frequently enlarging paradoxically or persisting for many years despite appropriate TB treatment and corticosteroid therapy. Most international guidelines recommend a 9-12 month course of TB treatment for central nervous system TB when the infecting Mycobacterium tuberculosis (M.tb) strain is sensitive to first-line drugs. However, there is variation in opinion and practice with respect to the duration of TB treatment in patients with tuberculomas or tuberculous abscesses. A major reason for this is the lack of prospective clinical trial evidence. Some experts suggest continuing treatment until radiological resolution of enhancing lesions has been achieved, but this may unnecessarily expose patients to prolonged periods of potentially toxic drugs. It is currently unknown whether persistent radiological enhancement of intracranial tuberculomas after 9-12 months of treatment represents active disease, inflammatory response in a sterilized lesion or merely revascularization. The consequences of stopping TB treatment prior to resolution of lesional enhancement have rarely been explored. These important issues were discussed at the 3rd International Tuberculous Meningitis Consortium meeting. Most clinicians were of the opinion that continued enhancement does not necessarily represent treatment failure and that prolonged TB therapy was not warranted in patients presumably infected with M.tb strains susceptible to first-line drugs. In this manuscript we highlight current medical treatment practices, benefits and disadvantages of different TB treatment durations and the need for evidence-based guidelines regarding the treatment duration of patients with intracranial tuberculous mass lesions.